Mini-plate fixation via sinus tarsi approach is superior to cannulated screw in intra-articular calcaneal fractures: A prospective randomized study. (10th August 2018) - Kir, Mustafa C; Ayanoglu, Semih; Cabuk, Haluk; Dedeoglu, Suleyman S; Imren, Yunus; Karslioglu, Bulent; Yuce, Ali; Gurbuz, Hakan
Objective: Intra-articular displaced calcaneal fractures are common fractures and are often treated with surgical interventions. Sinüs tarsi approach provides secure access to lateral wall and joint facets. The aim of the study is to compare cannulated screw (CS) fixation and mini-plate (MP) fixation via sinus tarsi approach with Sanders types 2 and 3 fracture of calcaneus. Methods: Sixty patients with Sanders types 2 and 3 calcaneal fracture underwent surgical intervention were randomly allocated into two groups as group MP fixation and group CS fixation regarding osteosynthesis method for 5-year period. Open reduction via sinüs tarsi approach was performed in both groups. Demographic variables, time to surgery (TS), operation duration (OD), length of hospital stay (LOS), surgical complications, and reoperations were recorded. Pre- and postoperative Gissane and Böhler angles; calcaneal length, height, and width; ankle anterior-posterior (AP) and lateral X-rays; and computed tomography were also recorded for radiological evaluation and fracture characteristics. Maryland Foot Score (MFS) was used to evaluate functional outcomes. Results: Preoperative age, type of fracture, calcaneal length, height, and Gissane and Böhler angles, TS, LOS, and OD were not different between the groups. The postoperative calcaneal widening was significantly better restored in group MP compared with that of group CS. The incidence of reoperation and algoneurodystrophy was statistically higher in group CS than group MP. MFS in group MP was also higher than group CS at final visit. Conclusion: MP fixation via sinus tarsi approach is superior to CS fixation in Sanders types 2 and 3 calcaneal fractures.